2022
DOI: 10.1007/s10067-022-06265-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of digital gangrene in connective tissue disorders: a longitudinal single-centre experience from Jodhpur, India

Abstract: Epidemiology, clinical presentation, and outcomes for digital gangrene in connective tissue disorders (CTD) remain underreported from tropical countries like India. In this series, we aimed to explore the clinical profile and outcomes of patients who presented with digital gangrene and a diagnosis of CTD. Hospital-based longitudinal observational study. Patients with digital gangrene and underlying diagnosis of CTD presenting to our tertiary-care centre in Jodhpur, India between1 st January 2018 and 31 st June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A single-centre study from Western India reported 22 cases of connective tissue disease-associated gangrene with the most common cause being mixed connective tissue disease. 16 They have variable presentations and outcomes ranging from complete recovery to amputation. These factors have been largely undefined in the literature.…”
Section: Demographicsmentioning
confidence: 99%
“…A single-centre study from Western India reported 22 cases of connective tissue disease-associated gangrene with the most common cause being mixed connective tissue disease. 16 They have variable presentations and outcomes ranging from complete recovery to amputation. These factors have been largely undefined in the literature.…”
Section: Demographicsmentioning
confidence: 99%
“…Connective tissue diseases like systemic lupus erythematosus (SLE), antiphospholipid antibody syndrome (APLA/APS), systemic sclerosis (SSc), and even systemic vasculitis may present with critical digital ischemia. About 9% of SSc and 5% of SLE patients present with digital gangrene [4]. APLA presents as pregnancy morbidity and/or thrombotic events due to the presence of antibodies like lupus anticoagulant, anticardiolipin antibodies, and anti-Beta2GP1 antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…A few other studies had also evaluated the aetiologies of gangrene in the context of rheumatic diseases (summarised in Table 1). [1][2][3][4] The prevalence and prognosis of peripheral gangrene vary with the underlying rheumatic disease. As an example, in patients with systemic sclerosis, data from the EUSTAR cohort reveal that nearly a tenth of patients experience digital gangrene.…”
mentioning
confidence: 99%